Differentiation grade is highly concordant between matched primary and metastatic colorectal cancer - Camilla M. Reehorst; Jennifer K. Mooi; Charles J. Uy; Kristen A. Needham; Sarah Ellis; Ian Y. Luk; Laura J. Jenkins; Rebecca Nightingale; Fiona Chionh; Andreas Behren; Niall C. Tebbutt; David S. Williams; et al. (Clinical & Experimental Metastasis, 2025)
Differentiation grade of colorectal cancers (CRC) is histologically defined by the proportion of the tumour which retains the glandular architecture of the normal colon. Poorly differentiated CRCs display loss of glandular architecture and canonical markers of colonic differentiation and are associated with increased metastatic capacity and poorer prognosis. It is currently unclear whether poorly differentiated cells within a heterogeneous primary tumour are more likely to establish metastases and if this cellular trait is conserved in the secondary tumours, or whether metastasis is largely stochastic, with most cells in the primary tumour harboring metastatic potential. To explore this, we examined the concordance in histological grade, expression of markers of colonic differentiation, and epithelial to mesenchymal transition (EMT) in 67 matched primary and metastatic CRCs. Tumour differentiation grade was scored categorically, and expression of differentiation and EMT markers were scored as continuous variables. In matched primary-metastatic pairs, tumour grade was concordant in 88% of cases (59/67 pairs), irrespective of the site of metastasis. In tumour pairs with discordant grade (n = 8), tumour grade was higher in the metastatic lesion in 6/8 (75%) cases. Consistent with the histological concordance, expression of the key driver of colonic differentiation (CDX2); colonic lineage-specific markers (VIL1, MUC2, SYN and CHG); and the markers of epithelial-to-mesenchymal transition (E-Cadherin and Vimentin) were highly concordant between matched primary and metastatic lesions. Finally, no staining of the squamous lineage marker Cytokeratin5/6 was observed in either primary or metastatic tumours. Tumour grade assessed histologically or using expression of markers of colonic differentiation or epithelial to mesenchymal transition was largely concordant between primary and metastatic CRC. These findings complement previously reported genomic similarities between primary and metastatic lesions and demonstrate that the histological grade of a primary tumour can in most cases inform the differentiation grade of associated metastatic lesions.